Monitoring of perfusion quality and prediction of donor heart function during ex-vivo machine perfusion by myocardial microcirculation versus surrogate parameters - Saemann, Lars; Wenzel, Folker; Kohl, Matthias; Korkmaz-İçöz, Sevil; Hoorn, Fabio; Loganathan, Sivakkanan; Guo, Yuxing; Ding, Qingwei; Zhou, Pengyu; Veres, Gábor; Karck, Matthias; Szabó, Gábor (The journal of heart and lung transplantation, 2021)
donation after circulatory death; ex-vivo machine perfusion; heart transplantation; myocardial microcirculation; risk prediction model